PEMBUATAN PROTOTIPE PEMBANGKIT LISTRIK HYBRID TENAGA MATAHARI DAN TENAGA ANGIN VAWT (VERTICAL AXIS WIND TURBINE) SINGLE TIPE SAVONIUS STAGE - , RIANTO; , Sugiyanto, S.T., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of fossil fuels for conventional power plants in the long term will drain oil, gas and coal resources. So renewable energy utilization that more environmentally friendly concepts such as wind and solar heat must be optimized. This is the our reason to make hybrid consep betwen wind and solar heat. This hybrid concept combining solar panels and turbines savonius as equipment conversion of solar energy and wind power. It is to gain a greater output than the solar panels and turbines savonius who work on their own. From measurement and data analysis, the electrical power generated by the hybrid system is 8.4 watt (lab.) and 7.54 watt (beach Depok). This value is greater if we compare it to the power generated by solar panels and wind turbines self, each of which produces a power of 7.466 Watt and 0.145Watt (beach Depok) and 0.814 watt (lab.).